EXTH-63. COMBINED INHIBITION OF TOP1 AND PARP: A NOVEL THERAPEUTIC STRATEGY FOR GBM WITH PTEN DEFICIENCY. (14th November 2022) - Kim, Olga; Butler, Madison; Robey, Robert; Chari, Raj; Sergi, Zach; Zhang, Meili; Pang, Ying; Yu, Guangyang; Zhang, Wei; Song, Hua; Davis, Dionne; Wang, Herui; et al.
Abstract: BACKGROUND: Glioblastoma (GBM) is the most aggressive and lethal type of brain tumor. Activation of PI3K/mTOR pathway along with the loss of its primary negative regulator, phosphatase and tensin homolog ( PTEN ), occurs in nearly 50% of GBM patients. As PTEN is known to promote DNA damage repair deficiency, here we investigated whether PTEN deficiency presents a vulnerability to a simultaneous induction of DNA damage and suppression of repair mechanisms by combining topoisomerase I (TOP1) and PARP inhibitors. METHODS: We used patient-derived GBM cells and stem-like cells to determine response to LMP400 (Indotecan), a novel non-camptothecin TOP1 inhibitor, and the PARP inhibitors Olaparib or Niraparib. Treatment efficacy was also determined using cell viability, cell cycle, DNA damage, repair, and apoptosis assays in a pair of isogenic PTEN-null and PTEN-WT glioma cell lines derived from a genetically engineered mouse GBM model. RNAseq analysis was performed to identify treatment-induced dysregulated pathways. RESULTS: PTEN-deficient cells are highly sensitive to LMP400 and PTEN rescue lessens sensitivity to the treatment. Combining LMP400 with PARP inhibitors, Olaparib or Niraparib, leads to synergistic cytotoxicity. LMP400/Niraparib combination induces G2/M cell cycle arrest, DNA damage, suppression of homologous recombination (HR)-related proteins and activation of caspase 3/7 activity significantly more in PTEN-null cells compared to isogenic PTEN-WT cells. Gene set enrichment analysis revealed suppression of cell cycle and DNA damage repair as well as activation of cell death pathways. Finally, CRISPR-Cas9 KO screening suggests that LMP400 is not likely to be a substrate for ABC transporters, suggesting the brain penetration and supporting the use in brain tumor patients. CONCLUSION: Combined inhibition of TOP1 and PARP induces synergistic antiglioma effects selectively in PTEN-null glioblastoma cells, providing a strong scientific premise for a clinical trial of combined treatment with LMP400 and Niraparib in a subset of GBM with PTEN deficiency.